From Paijanense to the Inca Empire in the Chicama Valley: State of the art, problems and proposals for archaeological research - Tantaleán, Henry (2022)
The main objective of this article is to present a synthesis of the various contributions that national and foreign researchers have made to the pre-Hispanic archaeology of the Chicama Valley, located in the Department of La Libertad, Peru. Through the analysis of the archaeological literature published to date, a balance and critical evaluation of current knowledge about the occupational history of the lower and middle Chicama valley. Finally, we outline new problems and working hypotheses for future archaeological investigations of this rich valley of the Peruvian north coast.